MicroRNAs in the Host-Apicomplexan Parasites Interactions: A Review of Immunopathological Aspects - Judice, Carla C.; Bourgard, Catarina; Kayano, Ana C. A. V.; Albrecht, Letusa; Costa, Fabio T. M. (Frontiers in Cellular and Infection Microbiology, 2016)
MicroRNAs (miRNAs), a class of small non-coding regulatory RNAs, have been detected in a variety of organisms ranging from ancient unicellular eukaryotes to mammals. They have been associated with numerous molecular mechanisms involving developmental, physiological and pathological changes of cells and tissues. Despite the fact that miRNA-silencing mechanisms appear to be absent in some Apicomplexan species, an increasing number of studies have reported a role for miRNAs in host-parasite interactions. Host miRNA expression can change following parasite infection and the consequences can lead, for instance, to parasite clearance. In this context, the immune system signaling appears to have a crucial role.